Building emancipatory peace through anarcho-pacifism. Issue 2 (4th May 2018) - Llewellyn, Joseph
ABSTRACT: The study of pragmatic nonviolence shows that nonviolence is often more effective than violence in its ability to overthrow governments and create more peaceable post-revolution societies. Nonviolent revolutionary movements and the findings from nonviolence research have contributed to a shift towards the development of an emancipatory peace or emancipatory politics. However, this shift is incomplete and cannot be completed using pragmatic nonviolence. This article argues that to move closer to an emancipatory politics, anarcho-pacifist nonviolence should be adopted. The article concludes that because an anarcho-pacifist framework would reject physical, structural and cultural violence, it must logically oppose the capitalist state. The article will finish by exploring how people could move beyond state-centric political forms by creating new emancipatory spaces, and therefore a more secure world.